Influence of environmental integrity on feeding, condition and reproduction of Phalloceros harpagos Lucinda, 2008 in the Tarumã stream micro-basin - Isabelle de Almeida Monaco; Yzel Rondon Súarez; Sidnei Eduardo Lima-Junior (Acta Scientiarum: Biological Sciences, 2014)
With the objective of evaluating the influence of the environmental integrity on feeding, condition factor and reproduction of Phalloceros harpagos, the species biology was analyzed in the Tarumã Stream micro-basin, Naviraí, Mato Grosso do Sul State (upper Paraná river). Samples were collected from 2007 to 2010, and biometric data of specimens was registered. Stomach and gonad were taken for the analysis of feeding and reproduction, respectively. The species is detritivore, showing a high flexibility in the diet. Debris and sediment, followed by plant and algae were the most ingested items. As for the condition factor, no definite pattern was observed in the values for both sexes, probably because the species has a long reproductive period. The frequency of occurrence distribution of gonad maturity stages indicated a greater number of immature females in the dry season at one of the least impacted sites. On the other hand, in the most affected site females were observed with increased fecundity. From the results obtained, it was found that the different levels of environmental degradation have no significant influence on feeding and condition factor, but rather probably exert influence on the reproduction of the species.